Experimental design for scientists and engineers - Usman, Mustofa; Elfaki, Faiz Ahmed Mohamed; Daoud, Jamal Ibrahim (IIUM Press, 2008)
This book is intended as an intermediate text for students in experimental design. The following can benefit from it if they have attended an introductory course in experimental design: •Undergraduate majors and postgraduate students in engineering, biotechnology, psychology, education and agriculture •Medical students •Graduate students who need an overview of the major topics in experimental design •Researchers and practitioners in different fields of study who need a comprehensive reference when conducting their experiments